The Effect of Moringa Oleifera Extract on Sperm Quality and Quantity of Diabetes Wistar Rat - Meldawati; Novita Dwi Febrianty; Herisa Putri Anggraini; Boyke Marthin Simbolon (Archives of The Medicine and Case Reports, 2021)
Diabetes mellitus is a condition in which blood glucose levels increase in a person's body which can result in chronic disorder. The effect of diabetes on a male reproductive system can affect sperm quality and disrupt the spermatogenesis process. Moringa oleifera leaves are rich in antioxidants such as flavonoids, vitamin A, vitamin E, and vitamin C, and contain selenium which helps lower bloodssugar levels. This study was conductedtto determine the effect of administering Moringa oleifera leaf extract on the quality andiquantity ofssperms in Wistar rats with diabetes mellitus. This research is an experimental studyiusing pre-andipost-randomized,controlled group design. This study examinediblood sugarllevels, density, motility, andiviability ofssperm cells. This experimental test was dividediinto 4 groups: one as a control group andtthree groups as treatment groups induced with alloxan and given ethanol extract of Moringa leaves with doses of 250, 500, and,750mg/kgBB. The results showed that the ethanol extract of Moringa leaves showedssignificant improvements in various doses (P-value ≤ 0.05).